Bronchiolitis obliterans syndrome after lung or haematopoietic stem cell transplantation: current management and future directions. Issue 3 (25th July 2022) - Glanville, Allan R.; Benden, Christian; Bergeron, Anne; Cheng, Guang-Shing; Gottlieb, Jens; Lease, Erika D.; Perch, Michael; Todd, Jamie L.; Williams, Kirsten M.; Verleden, Geert M.
Bronchiolitis obliterans syndrome (BOS) may develop after either lung or haematopoietic stem cell transplantation (HSCT), with similarities in histopathological features and clinical manifestations. However, there are differences in the contributory factors and clinical trajectories between the two conditions. BOS after HSCT occurs due to systemic graft- versus -host disease (GVHD), whereas BOS after lung transplantation is limited to the lung allograft. BOS diagnosis after HSCT is more challenging, as the lung function decline may occur due to extrapulmonary GVHD, causing sclerosis or inflammation in the fascia or muscles of the respiratory girdle. Treatment is generally empirical with no established effective therapies. This review provides rare insights and commonalities of both conditions, which are not well elaborated elsewhere in contemporary literature, and highlights the importance of cross disciplinary learning from experts in other transplant modalities. Treatment algorithms for each condition are presented, based on the published literature and consensus clinical opinion. Immunosuppression should be optimised, and other conditions or contributory factors treated where possible. When initial treatment fails, the ultimate therapeutic option is lung transplantation (or re-transplantation in the case of BOS after lung transplantation) in carefully selected candidates. Novel therapies under investigation include aerosolised liposomal cyclosporine, Janus kinase inhibitors, antifibrotic therapies and (in patients with BOS after lung transplantation) B-cell-directed therapies. Effective novel treatments that have a tangible impact on survival and thereby avoid the need for lung transplantation or re-transplantation are urgently required. A review focusing on novel treatment approaches for bronchiolitis obliterans syndrome, to reverse the pathological changes and thereby impact tangibly on survival or need for subsequent lung transplantation, and improve patients' quality of life https://bit.ly/3lCIB0x